BUSINESS PROCESS RE-ENGINEERING THROUGH 3 HARD Ss McKINSEY FRAMEWORK AS WORKING CAPITAL MANAGEMENT IMPROVEMENT PROPOSAL (CASE STUDY: PT. XYZ – 2020/2021) - Prasetyo, Wibisono Adhi; Yudoko, Gatot (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
Due to the negative operating cash flow, working capital's unsatisfactory performance indicates that internal business processes exist. Meanwhile, the COVID-19 pandemic urges the management to be wiser in making decisions, primarily to support better working capital management. They cannot rely forever on its aggressive capital structure. Accordingly, the management committed to carrying out operation improvement related to working capital management. This decision is the background of this research to identify and analyze the root cause problems and improvement plan issues. Further investigations regarding the business issue are conducted, and business process re-engineering through the 3 hard Ss framework is selected as the research design. These frameworks are approached due to their capability to map the thorough process and link them to one another. These combination improvement ideas over the ineffective and inefficient activities could be blended while organized to be aligned with the organizational directions. This research is conducted through a semi-structured interview to explore the company conditions and uses secondary data to gather the information and strengthen the evidence. At least 14 ineffective and inefficient activities were then carried out a root-cause analysis to determine the source of the problem that had to be eliminated. Based on these findings, four management improvements are suggested: Production management, Receivable Management, Payable management, and Cash flow control and monitoring translated into action plan strategies, procedures, and tools which are equipped structurally and systems.